Effect of Low-Load Blood Flow Restriction Training After Anterior Cruciate Ligament Reconstruction: A Systematic Review - Baris B. Koc; Alexander Truyens; Marion J.L.F. Heymans; Edwin J.P. Jansen; Martijn G.M. Schotanus (International Journal of Sports Physical Therapy)
# Background